A six‐factor asset pricing model: The Japanese evidence. Issue 1 (28th February 2021) - Roy, Rahul
Abstract: The fundamental research question associated with the asset pricing framework relates to the risk and return relationship in return predictability. We introduce the human capital component to the Fama–French five‐factor model and derive an equilibrium six‐factor asset pricing model in an intertemporal framework. The study comprises the Japanese monthly time‐series dataset for 24 years spanning November 1990 to December 2017. The Generalized method of moments estimation and Gibbons‐Ross‐Shanken test results confirm that the six‐factor model yields better estimates and equally outperforms the Fama–French three‐factor, Carhart four‐factor, and Fama–French five‐factor models in explaining the variation in excess return on Fama–French variant portfolios. The core results and findings hold when we use labor income growth as an alternate measure of human capital in the six‐factor asset pricing model.